2019
DOI: 10.1371/journal.pone.0218552
|View full text |Cite
|
Sign up to set email alerts
|

SNP-based mixed model association of growth- and yield-related traits in popcorn

Abstract: The identification of the genes responsible for complex traits is highly promising to accelerate crop breeding, but such information is still limited for popcorn. Thus, in the present study, a mixed linear model-based association analysis (MLMA) was applied for six important popcorn traits: plant and ear height, 100-grain weight, popping expansion, grain yield and expanded popcorn volume per hectare. To this end, 196 plants of the open-pollinated popcorn population UENF-14 were sampled, selfed (S 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 70 publications
1
11
0
Order By: Relevance
“…Analysis of population genetic structure is a major area of interest within the field of genetics and bioinformatics, which is a common practice in genome-wide studies, including association mapping, ecology, and evolution studies in crop species such as maize (Li et al, 2019;Mafra et al, 2019;Maldonado et al, 2019;Wang et al, 2019). The present study proposed an MLbased analysis of population structure and individual assignment usually performed in several data-intensive biological fields.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of population genetic structure is a major area of interest within the field of genetics and bioinformatics, which is a common practice in genome-wide studies, including association mapping, ecology, and evolution studies in crop species such as maize (Li et al, 2019;Mafra et al, 2019;Maldonado et al, 2019;Wang et al, 2019). The present study proposed an MLbased analysis of population structure and individual assignment usually performed in several data-intensive biological fields.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, genotype-phenotype studies for quantitative traits at the genome level usually require high-density genetic marker panels, i.e., a large number of markers throughout the genome and large population sizes to obtain sufficient power and prediction resolution [1,2]. The development of several genotyping platforms through high-density single nucleotide polymorphism (SNP) arrays, such as genotyping-by-sequencing (GBS) or SNP chips, has enabled the identification of quantitative trait loci (QTL) for different target traits in various plant species [3][4][5][6]. Silva-Junior et al [7], for instance, developed a genome-wide SNP chip for multiple species of Eucalyptus, which has been effective for genomic studies in a wide variety of economically important eucalypt species and their hybrids, including Eucalyptus grandis, Eucalyptus urophylla, Eucalyptus nitens and Eucalyptus globulus [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…A successful tool to explain the genetic basis of complex traits in association studies, which allow the identification of quantitative trait loci (QTLs) based on the significant associations between genotypic markers and phenotypic data [ 8 ]. The identification of QTLs related to PE and GY has been reported in several studies, for example, simple sequence repeat (SSR) and single-nucleotide polymorphism (SNP) markers [ 5 , 8 , 9 , 10 , 11 , 12 ]. Thakur et al [ 10 ] identified three QTLs associated (using SSR markers) with the popping volume, which covers 78% of total phenotypic variance.…”
Section: Introductionmentioning
confidence: 99%
“…The SNP has been widely used in association studies for the detection of a large number of QTLs and candidate genes involved in the yield and growth [ 8 , 14 , 15 ]. Despite their wide usage, association studies have been criticized, since according to certain studies, they are inefficient in detecting the total genetic variation of complex traits [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%